Influence of mental energy on volleyball competition performance: a field test - Shiow-Fang Shieh; Frank J.H. Lu; Diane L. Gill; Chih-Hsuan Yu; Shu-Ping Tseng; Meisam Savardelavar (PeerJ, 2023)
Athletic mental energy is a newly emerging research topic in sport science. However, whether it can predict objective performance in competition remains unexplored. Thus, the purpose of this study was to examine the predictability of mental energy on volleyball competition performance. We recruited 81 male volleyball players (Mage = 21.11 years ± SD = 1.81) who participated in the last 16 remaining teams in a college volleyball tournament. We assessed participants’ mental energy the night before the competition and collected their competition performance over the next 3 days. We used six indices of the Volleyball Information System (VIS) developed by the International Volleyball Federation (FIVB) to examine its associations with mental energy. All six factors of mental energy –motivation, tirelessness, calm, vigor, confidence, and concentration correlated with volleyball competition performance. Further, a hierarchical regression found mental energy predicted volleyball receivers’ performance (R2 = .23). The findings advance our knowledge of mental energy and objective performance in competition. We suggest that future studies may examine the effects of mental energy on different sports with different performance indices.